Identification of a novel TMEM106B-ROS1 fusion variant in lung adenocarcinoma by comprehensive genomic profiling. Issue 3 (June 2015) - Ou, Sai-Hong Ignatius; Chalmers, Zachary R.; Azada, Michele C.; Ross, Jeffrey S.; Stephens, Philip J.; Ali, Siraj M.; Miller, Vincent A.
Abstract Objectives ROS1-rearranged non-small cell lung cancer (NSCLC) is a unique molecularly defined yet heterogeneous subset of NSCLC. To date 12 known fusion partners of ROS1 in NSCLC have been reported. While crizotinib, a multi-targeted ALK/ROS1/MET tyrosine kinase inhibitor (TKI), has demonstrated significant clinical activity in ROS1-rearranged NSCLC, no companion diagnostic assay has been approved for the detection of ROS1-rearrange NSCLC by the US FDA. Comprehensive genomic profiling (CGP), a subtype of clinical next-generation sequencing (NGS), offers a uniquely comprehensive and convenient approach to detect the ever-increasing and "druggable" receptor-kinase rearrangements being discovered in lung cancer. Materials and methods We identified a novel ROS1 fusion variant (TMEM106B-ROS1) in a stage IV adenocarcinoma of the lung never-smoker female patient during routine genomic profiling (FoundationOne®). This novel TMEM106B-ROS1 fusion variant is generated by the fusion of exons 1–3 of TMEMB106B on chromosome 7p21 to the exons 35–43 of ROS1 on chromosome 6q22. The predicted TMEM106-ROS1 protein product contains 540 amino acids comprising of the N-terminal amino acids 1–73 of TMEMB106 and C-terminal amino acids of 1881–2341 of ROS1. Although there is no predicted "coiled-coil" domain in the N-terminal domain of TMEM106B, the N-terminal domain of TMEM106B is involved in homo- and hetero-dimerization with other TMEM106 family members. Conclusions TMEM106B-ROS1 is a novel ROS1 fusion variant in NSCLC identified by comprehensive genomic profiling and should be included in any ROS1 detecting assay that depends on identifying the corresponding fusion partners such as reverse transcriptase-polymerase chain reaction (RT-PCR).